Is utilisation of computed tomography justified in clinical practice? Part 1: application in the emergency department. - Sun, Zhonghua; Ng, K.; Vijayananthan, A. (Singapore Medical Association, 2010)
Computed tomography (CT) is currently a widely available imaging technique in clinical practice. Technical developments of CT imaging, especially the emergence of multislice CT, with increased scanning speed and volume, higher spatial and temporal resolution, have significantly enhanced the diagnostic value of CT in many clinical applications. CT has become an important diagnostic imaging modality in the emergency department, with high diagnostic accuracy and efficacy in both traumatic and non-traumatic conditions. There is however a growing concern about the risk of associated radiation exposure in the population exposed to CT examination. Justification of the application of CT is one of the main principles that physicians need to be aware of when choosing CT as the first line technique for diagnosis. This article reviews the clinical applications of CT imaging in the emergency department, with focus on patients presenting with headache, repeat and multiple CT imaging and whole body screening for trauma patients, and explore whether the applications are clinically justified.